Analisis financiero y su relación en la toma de decisiones de matizados y pinturas El Moreno F&L EIRL, periodo 2020-2021 - Burga Rodriguez, Pamela Geraldine (2024)
The main objective of the research was to determine how financial analysis is related to decision making in the company Matizados y Pinturas El Moreno F&L EIRL, in the city of Iquitos, periods 2020 and 2021, with a type of quantitative non-design research. experimental longitudinal design type of descriptive scope, the study population was the 04 financial statements of the company for the period 2020 and 2021, in addition to the interview carried out with 21 workers, the document analysis technique and the survey were used. The results found show that 61.9% of those surveyed claimed to have permanent knowledge about the financial situation of the company and with respect to Current Assets, Cash and Cash Equivalent, we have 55.56% in 2020 and 65.60% in 2021; showing that cash and equivalents have experienced a significant increase in proportion to total assets, indicating greater liquidity in 2021; concluding that the value of the Rho Spearman correlation coefficient between Financial Analysis and Decision Making is 0.758. This indicates a high positive correlation, which means that as a deeper financial analysis is carried out, strategic decision making in the company improves, in addition the financial ratios show improvements in liquidity, operational efficiency, management of inventories and profitability for the company in 2021 compared to 2020.